Forage tree legumes in tropical agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Forage tree legumes in tropical agriculture edited by R C Gutteridge and H M Shelton 1993 400pp ISBN 0 85198 868 7 Pbk price UKL24.00 CAB International, Wallingford Oxon OX10 ODE, UK